2010
DOI: 10.1007/s00420-010-0571-x
|View full text |Cite
|
Sign up to set email alerts
|

Serial testing with the interferon-γ release assay in Portuguese healthcare workers

Abstract: ObjectivesEvidence for the utility of the new Mycobacterium tuberculosis (MTB) specific IFN-γ release assays in diagnosing latent tuberculosis infection (LTBI) is growing. However, data concerning conversion and reversion rates in serial testing of healthcare workers (HCWs) with an interferon-γ release assay are sparse.MethodsBetween February 2007 and September 2009, 670 HCWs in the University Hospital of Porto, Portugal were tested at least twice with QuantiFERON-TB® Gold In-Tube (QFT) for LTBI. The tuberculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…In so far our study corroborates the observations of other studies [23-25]. A high reversion rate of positive IGRA was reported by other studies before [26-33]. As no active TB cases were observed in our study, information for the clinical interpretation of a reversion in IGRA cannot be derived from our data.…”
Section: Discussionsupporting
confidence: 92%
“…In so far our study corroborates the observations of other studies [23-25]. A high reversion rate of positive IGRA was reported by other studies before [26-33]. As no active TB cases were observed in our study, information for the clinical interpretation of a reversion in IGRA cannot be derived from our data.…”
Section: Discussionsupporting
confidence: 92%
“…In addition we identified three studies on cost-effectiveness of IGRAs in HCWs and three studies on feasibility and test implementation. Finally, two new serial testing studies were identified by 1 October 2010, giving a total of 50 studies of IGRAs in HCWs 20 21. The characteristics of the cross-sectional and serial testing studies identified in this review are shown in tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of within-subject variability that we determined approximates the proposed borderline zones. Three recent serial testing studies among German and Portuguese HCWs demonstrated that the implementation of a QFT borderline zone of 0.2 to 0.7 IU/ml may safely reduce the rate of inconsistent results (26,29,31). For the T-SPOT, evidence for the safety of a specific borderline zone is sparse.…”
Section: Discussionmentioning
confidence: 99%